Engaging Cervical Spinal Cord Networks to Reenable Volitional Control of Hand Function in Tetraplegic Patients. (November 2016) - Lu, Daniel C.; Edgerton, V. Reggie; Modaber, Morteza; AuYong, Nicholas; Morikawa, Erika; Zdunowski, Sharon; Sarino, Melanie E.; Sarrafzadeh, Majid; Nuwer, Marc R.; Roy, Roland R.; Gerasimenko, Yury
Background. Paralysis of the upper limbs from spinal cord injury results in an enormous loss of independence in an individual's daily life. Meaningful improvement in hand function is rare after 1 year of tetraparesis. Therapeutic developments that result in even modest gains in hand volitional function will significantly affect the quality of life for patients afflicted with high cervical injury. The ability to neuromodulate the lumbosacral spinal circuitry via epidural stimulation in regaining postural function and volitional control of the legs has been recently shown. A key question is whether a similar neuromodulatory strategy can be used to improve volitional motor control of the upper limbs, that is, performance of motor tasks considered to be less "automatic" than posture and locomotion. In this study, the effects of cervical epidural stimulation on hand function are characterized in subjects with chronic cervical cord injury. Objective. Herein we show that epidural stimulation can be applied to the chronic injured human cervical spinal cord to promote volitional hand function. Methods and Results. Two subjects implanted with a cervical epidural electrode array demonstrated improved hand strength (approximately 3-fold) and volitional hand control in the presence of epidural stimulation. Conclusions. The present data are sufficient to suggest that hand motor function in individuals with chronic tetraplegia can be improved with cervical cord neuromodulation and thus should be comprehensively explored as a possible clinical intervention.